Chemical Constituents and Antioxidant Activities of Haplophyllum Laeviusculum C.C. Towns. and H. Villosum (Bye.) Don. - Parhoodeh, Parimah (2010)
The genus Haplophyllum from the Rutaceae family is made up of about 70 species distributed mainly around the Mediteranean countries and thirty of them are found in Iran. Chemical literature survey revealed that the genus contains various interesting secondary metabolites such as alkaloids, lignans, coumarins and triterpenes. In this study two species of the plant, Haplophyllum laeviusculum and Haplophyllum villosum collected from West Azarbayejan province in Iran, were investigated in detailed. Literature search indicated that there have been no previous reports on chemical compounds and biological activities of these two plants. A chemical study on the aerial parts of the plants has resulted in the isolation and structural elucidation of ten compounds. These compounds were isolated by different chromatographic techniques such as gravity column chromatography, vacuum chromatography, Thin Layer Chromatography (TLC), Preparative Thin Layer Chromatography (PTLC) and Chromatotron. The structures of these compounds were identified by using spectroscopic methods which are UV, IR, NMR, MS and also by comparison with previous work. The crude extracts and isolated compounds were tested for antioxidant activities by using DPPH (1, 1-Diphenyl- 2-pircrylhydrazyl) free radical scavenging activity. Detailed chemical studies on Haplophyllum laeviusculum afforded two triterpenoids (- sitosterol (62) and campesterol (63)) and three alkaloids, skimmianine (5), lunamarine (64) and ribalinidine (65)). Meanwhile extraction and separation of the aerial parts of Haplophyllum villosum gave one alkaloid, haplamine (67)), two lignans eudesmin (66) and eudesmin A (70)) and two coumarins, scopoletin (69) and umbelliferone (68). Both methanol crude extracts of these two species possess strong antioxidant activities against DPPH stable free radical. The ethyl acetate crude extracts of Haplophyllum laeviusculum and chloroform crude extracts of Haplophyllum villosum showed moderate activities against DPPH stable free radical test with IC50 values of less than 400 g/ml. Other crude extracts and isolated compounds such as skimmianine (5), lunamarine (64) and ribalinidine (65), eudesmin (66) and haplamine (67), showed weak radical scavenging activities.